Efficacy and Safety of [225Ac]Ac-PSMA-617 Augmented [177Lu]Lu-PSMA-617 Radioligand Therapy in Patients with Highly Advanced mCRPC with Poor Prognosis - Florian Rosar; Jonas Krause; Mark Bartholomä; Stephan Maus; Tobias Stemler; Ina Hierlmeier; Johannes Linxweiler; Samer Ezziddin; Fadi Khreish (MDPI AG, 2021)
The use of 225Ac in prostate-specific membrane antigen (PSMA)-targeted radioligand therapy (RLT), either as monotherapy or in combination with 177Lu, is a promising therapy approach in patients with metastatic castration-resistant prostate carcinoma (mCRPC). In this study, we report the efficacy and safety of [225Ac]Ac-PSMA-617 augmented [177Lu]Lu-PSMA-617 RLT in 177Lu-naive mCRPC patients (n = 15) with poor prognosis (presence of visceral metastases, high total tumor burden with diffuse bone metastases or a short PSA doubling time of <2 months). Biochemical (by PSA serum value) and molecular imaging response (by [68Ga]Ga-PSMA-11 PET/CT) was assessed after two cycles of [177Lu]Lu-PSMA-617 RLT, with at least one [225Ac]Ac-PSMA-617 augmentation. In addition, PSA-based progression-free survival (PSA-PFS), overall survival (OS) and toxicity (according to CTCAE) were analyzed. We observed a biochemical- and molecular imaging-based partial remission in 53.3% (8/15) and 66.7% (10/15) of patients, respectively. The median PSA-PFS and OS was 9.1 and 14.8 months, respectively. No serious acute adverse events were recorded. Two out of fifteen patients experienced grade 3 anemia. No other grade 3/4 toxicities were observed. RLT-related xerostomia (grade 1/2) was recorded in 2/15 patients. Our data showed a high clinical efficacy with a favorable side effects profile of [225Ac]Ac-PSMA-617 augmented [177Lu]Lu-PSMA-617 RLT in this highly challenging patient cohort.